Efektivitas Pemberdayaan UMKM Melalui Pendampingan Komunitas untuk Pengembangan Industri Kreatif Budaya Tionghoa sebagai Destinasi Wisata Kota Tangerang - Aprilyanti, Rina; Lianah; Etty Herijawati (LP3kM Buddhi Dharma University, 2025)
This study aims to identify the influence of Business Assistance, Cultural Product Innovation, and Community Engagement on the Sustainability of Chinese culture based MSMEs in Tangerang City, with Tourism Attractiveness as a mediating variable. Tangerang City has significant potential to develop creative products rooted in Chinese culture; however, many MSMEs face challenges such as limited managerial capacity, product innovation, and community involvement in promoting cultural tourism. The study employs a quantitative approach using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) method to test the relationships among variables. Data were collected through a survey of 200 Chinese culture–based creative MSME actors selected via purposive sampling. The findings reveal that Business Assistance, Cultural Product Innovation, and Community Engagement exert a positive and significant effect on MSME Sustainability, with contributions of 21.5%, 19.8%, and 23.0%, respectively. Moreover, Tourism Attractiveness was found to partially mediate these relationships, further strengthening their positive impact on MSME sustainability. These results carry important practical and policy implications. First, the findings may serve as a foundation for local governments to design integrated MSME empowerment programs through business training, product innovation, and community collaboration. Second, the study provides a basis for developing culture based MSME assistance practices that not only enhance business capacity but also reinforce local cultural identity to expand tourism attractiveness. Thus, this research makes a direct contribution to public policy and culture based MSME empowerment strategies, with the potential to improve local economic competitiveness while preserving cultural heritage in Tangerang City.